The Relationship Between Fluid Restriction and Thirst Distress in Patients with Heart Failure - Nindithya Wahyu Pradina; Tuti Herawati; Amelia Kimin (GLOBAL HEALTH SCIENCE GROUP, 2026)
Heart failure is a chronic cardiovascular disease that is often accompanied by thirst distress. Fluid restriction, which is commonly recommended as part of heart failure management, may increase thirst and potentially affect patients' comfort and quality of life. To identify the relationship between fluid restriction and thirst distress in patients with heart failure based on a literature review. This literature review was conducted using a systematic approach based on the PRISMA guidelines. Literature searches were performed in ProQuest, PubMed, Scopus, ScienceDirect, and JSTOR databases. A total of 10,762 articles were initially identified. Eligible articles included cross-sectional studies, cohort studies, and randomized controlled trials (RCTs) published between 2016 and 2026 that examined fluid restriction and thirst distress in patients with heart failure. Following the removal of duplicates and screening based on predefined inclusion and exclusion criteria, study quality was assessed using the JBI Critical Appraisal Checklist. A total of eight articles met the inclusion criteria and were analyzed narratively. Fluid restriction was associated with increased thirst intensity and thirst distress among patients with heart failure. Several studies reported that patients undergoing fluid restriction experienced higher thirst distress scores than those without fluid restriction. However, some studies did not find a significant association, particularly in populations with similar participant characteristics. In addition to fluid restriction, thirst distress was influenced by various factors, including diuretic use, urea levels, psychological conditions, and patients' clinical status. Fluid restriction is associated with increased thirst intensity and thirst distress in patients with heart failure. However, thirst distress is also influenced by various other factors.